Experimental investigation of the response of precast segmental columns subjected to impact loading - Zhang, Xihong; Hao, Hong; Li, C. (Elsevier, 2016)
Although precast concrete segmental columns have been more and more widely used in constructions, there is a lack of study on its behaviour under dynamic loading especially impact loading. In this paper, the fundamental behaviour of precast segmental columns under impact loading is investigated through laboratory tests. Scaled precast segmental columns with unbonded posttensioning tendon were constructed and tested using pendulum impact system. Two segmental columns of the same height, but with different numbers of precast segments were designed and tested. A conventional monolithic reinforced concrete (RC) column was also casted and tested as a reference column to compare the performance with segmental columns under impact loading. The impact load time history and column displacement time histories at column top, mid-height and column base were recorded. The deformation-to-failure processes of the columns were monitored by a high-speed camera, and used to investigate the response of different columns under impact loads. The test results showed the segmental column is more flexible than monolithic column, which leads to lower peak impact force, but longer duration compared to those on the monolithic RC column. It was also found that compared with monolithic columns, segmental columns show better performance against impact load with better self-centring capability, similar energy dissipation capability and less residual displacement and concrete damage.